Statement of Problem, Research Aims and Research Objectives - Norahim, Norazuna (Universiti Malaysia Sarawak, 2012)
One of the critical elements in the examination of an MA or a Ph.D. thesis is that there should be a clear linkage between its various components. The statement of a research project relates closely with research aim(s) and objectives. Research aims and objectives will set the direction and scope of the project, and should be aligned with research gap identified from the literature on the subject. Likewise, establishing gap in research will provide the significance of the study (i.e. contribution to the exiting knowledge in the field under study). This workshop aims to provide a deeper understanding of the essence of various components outlined in the introductory chapter of a thesis. A checklist of what examiners look for in a thesis will also be highlighted.